Analisis Persepsi Nilai dan Kepercayaan Terhadap Kepuasan Pelanggan Kecap CV. Sinar Abadi - Fran Wijaya, Tommy (Jurnal Akutansi Manajemen Ekonomi Kewirausahaan (JAMEK), 2023)
This study examines the impact of perceived value and trust on customer satisfaction with CV Sinar Abadi, a company producing Sinar Abadi brand soy sauce. Amidst intense competition in the soy sauce industry, CV Sinar Abadi recognizes the importance of retaining loyal customers to maintain its market position. The study aims to provide empirical evidence and analyze the effects of value perception and trust on customer satisfaction for CV Sinar Abadi’s soy sauce. Using a quantitative approach, data was analyzed through multiple linear regression via SPSS. Findings indicate that both perceived value and trust significantly influence customer satisfaction. Additionally, when combined, perceived value and trust substantially impact overall customer satisfaction with CV Sinar Abadi's soy sauce. These results highlight the critical role of both value perception and trust in fostering customer loyalty and satisfaction in a competitive market.